Bacteriological and Phytochemical Assessment of Ficus asperifolia Linn. Infusion. (14th May 2020) - Fasina, Kolapo Ayoola; Adesetan, Titilayo O.; Oseghale, Faithfulness; Egberongbe, Haneefat O.; Aghughu, O. O.; Akpobome, Fred A.
Abstract : Ficus asperifolia Linn. known as "Eepin" in Yoruba language, or sand paper tree, is a monoecious fig tree whose leaves, bark, seeds, and roots have been used locally in treating many infectious and noninfectious diseases. The study is aimed at investigating the bacteriological and phytochemical potential of Ficus asperifolia Linn. The roots of the plant were harvested and washed, and phytochemical analysis was carried out using standard analytical techniques. Infusion was aseptically prepared, and incubation for 24 hours and microbiological analysis were carried out using the pour plate method on Plate Count Agar (PCA) and Nutrient Agar (NA). Microorganisms were subcultured and identified using morphological and biochemical tests according to "Bergey's Manual of Determinative Bacteriology." Phytochemical analysis of the fresh and dry roots revealed the presence of alkaloids, cardenolides, and saponins, while anthraquinones and tannins were absent. Total heterotrophic bacteria count on PCA was 5.6 × 10 5 CFU / ml, while on NA, it was 2.3 × 10 5 CFU / ml, and four classes of bacteria were isolated including Klebsiella sp., Escherichia coli, Proteus sp., and Bacillus sp. Although the presence of medicinal phytochemicals in F. asperifolia Linn. indicates strong potentials for its use in infusions, the presence of potential pathogens found in the infusions makes it unsafe for consumption.